The Symbolic Communication of Kenduri : Ritual Adaptation, Identity Formation, and Social Cohesion in Javanese Diaspora Communities - Khairani, Leylia; Hendra, Yan (JURNAL PENELITIAN, 2025)
Kenduri , a form of slametan ritual rooted in Javanese traditions, integrates religious devotion with cultural and social dimensions. It symbolizes collective identity, sustains moral values, and links individuals to the divine. This study aimed to understand how kenduri functions as a symbolic communication system, transmitting meanings through foods, prayers, spatial arrangements, and adaptive practices. Ethnographic fieldwork was conducted in a Javanese diaspora community in North Sumatra, employing participant observation, in-depth interviews, and document analysis. Data were coded and thematically analyzed to uncover how participants interpret and negotiate the ritual’s symbolic elements. The results indicate that kenduri ’s constituent symbols—such as bubur merah putih and ingkung—convey notions of purity, spirituality, and life cycles, while seating arrangements and prayer recitations foster communal unity and reinforce moral cohesion. Local adaptations, including the incorporation of regional ingredients, demonstrate kenduri ’s resilience in a pluralistic environment. These findings reveal kenduri as a dynamic communicative event, linking cultural heritage with contemporary realities and maintaining relevance despite historical shifts and demographic changes. By underscoring the ritual’s integrative and adaptive nature, this research advances our understanding of how religious practices generate and convey meaning across diverse contexts. Ultimately, kenduri exemplifies how ritual communication can preserve core values, reinforce community solidarity, and guide spiritual engagement, offering valuable insights for future comparative and interdisciplinary studies.